Shifting value stream patterns along the product lifecycle with digital twins - Schleich, Benjamin; Dittrich, Marc-André; Clausmeyer, Till; Damgrave, Roy; Erkoyuncu, John Ahmet; Haefner, Benjamin; Lange, Jos de; Plakhotnik, Denys; Scheidel, Wieben; Wuest, Thorsten (Elsevier, 2020)
The concept of digital twins promises high potentials for product design, manufacturing, user experience and recycling. Thus, digital twins have received increasing interest in academia and industry. However, the actual benefits of digital twins remain in many cases unclear. This article aims to summarize selected recent developments in this field and demonstrate use cases from different phases of the product lifecycle. For that purpose, examples from the design, manufacturing, use and recycling phase are presented. In a subsequent discussion, ideas for new value stream patterns using digital twins are envisioned and research questions are derived
Keywords: Recycling; Cyber-physical systems; Manufacturing; Digital twin